Conflict Resolution Techniques for High-Pressure Cabin Environments: A Service Recovery Framework - Maida Nkonye Asata; Daphine Nyangoma; Chinelo Harriet Okolo (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In the dynamic and confined environment of commercial aircraft cabins, conflicts can arise swiftly and unexpectedly, often fueled by stress, cultural differences, operational delays, or unmet service expectations. These high-pressure situations pose significant challenges to cabin crew, who must maintain safety, ensure service continuity, and manage emotional responses among passengers. This explores conflict resolution techniques specifically adapted for high-pressure cabin environments and proposes a service recovery framework designed to support cabin crew in managing and recovering from in-flight disputes effectively. Drawing from communication theory, emotional intelligence, and service recovery literature, the framework emphasizes three critical stages: immediate de-escalation, problem resolution, and post-incident recovery. Techniques such as active listening, assertive-yet-empathetic communication, and the CLEAR model (Clarify, Listen, Empathize, Act, Reassure) are integrated to guide crew responses in real time. Cultural sensitivity and non-verbal communication also emerge as crucial elements in mitigating misunderstandings and restoring passenger confidence. The framework is further supported by structured crew training, standard operating procedures, and performance feedback mechanisms. Case examples from leading airlines such as Delta Air Lines and Singapore Airlines illustrate the practical application of these strategies in real-world contexts, highlighting the impact of proactive conflict management on service quality and passenger satisfaction. The findings suggest that airlines investing in comprehensive service recovery training and empowering their crew with adaptive conflict resolution skills can enhance passenger trust, minimize service disruptions, and strengthen brand reputation. Future research is encouraged to explore technology-enhanced conflict mediation tools, such as AI-driven decision support systems and real-time behavioral monitoring, as well as cross-cultural variations in conflict perception and resolution preferences. Ultimately, embedding conflict resolution within a broader service recovery framework enables airlines to transform in-flight tensions into opportunities for reinforcing customer loyalty.